52.4k views
0 votes
Simplify to create an equivalent expression 2-6(-5t+1)

User Tisho
by
6.1k points

2 Answers

6 votes

Answer:

30t - 4

Step-by-step explanation:

Expand -6(-5t + 1): 30t - 6

= 2 + 30t - 6

Simplify 2 + 30t - 6

= 30t - 4

M.

User Mike Ward
by
5.4k points
4 votes

Answer:

30t - 4

Step-by-step explanation:

Remember to follow PEMDAS. First, distribute -6 to all terms within the parenthesis:

2 -6(-5t + 1) = 2 + (-6 * -5t) + (-6 * 1)

2 + (30t) + (-6) = 2 + 30t - 6

Simplify. Combine like terms:

2 + 30t - 6 = 30t + (-6 + 2) = 30t - 4

30t - 4 is your answer.

~

User Satish Sharma
by
6.1k points